Improvement of zefir production by addition of the developed blended fruit and vegetable pasteinto its recipe - Zahorulko, Andreii; Zagorulko, Aleksey; Kasabova, Kateryna; Shmatchenko, Nataliа (Eastern-European Journal of Enterprise Technologies, 2020)
A method has been developed for the production of a fruit and vegetable paste-like semi-finished product based on an Antonovka apple, Muscat pearl pumpkin and Bona beet. The method is characterized by concentration in gentle temperature conditions (50...55 °C) in a rotary film apparatus to content of 45 % dry matters lasting 1.25...2.0 min. The structural and mechanical characteristics of the mashed potatoes of the components of raw materials and blended concentrated pastes by the developed method are determined. The structure of the developed fruit and vegetable paste was confirmed to be strengthened, since its maximum dynamic viscosity is 283 Pa∙s, which is 1.9 times more compared to the control (apple paste). Thus, a rational composition is selected for further research with the following components in the paste: apple – 60 %; pumpkin – 20 %, beets – 20 % (composition 1). This paste in comparison with the control has a high content of functional physiological ingredients and has good organoleptic properties. The feasibility of using the developed fruit and vegetable paste in composition of zefirs (composition 1) in the amount of 75 % replacement of apple puree is confirmed. The selected zefir sample differs in its original organoleptic properties. This ensures an increase in the effective viscosity (ηef, Pa∙s) of zefirs with the replacement of 75 % of apple puree with blended paste, compared to control (zefirs without additives) from 391 to 782. The plastic strength (Pk) also increases depending on the duration: 75 % – 54.2 kPa (control sample – 47 kPa), which is generally a positive phenomenon from a technological point of view. Such a solution will provide consumers with food products with physiologically functional ingredients of natural origin, subject to the partial or complete replacement of individual raw materials with blended fruit and vegetable compositions, providing an increase in their functional value